Odpowiedź :
Odpowiedź:
a) ( p +4) ( p-2)= p²-2p +4p -8= p²+2p -8
b) ( - 3 +a ) ( a-4)= -3a +12 +a²-4a = a²-7a +12
c) ( 2x -5)( x+3)= 2x²+6x-5x -15= 2x²+x -15
d) ( 4m +1)( 2m-5)= 8m²-20m +2m -5= 8m²-18m -5
e) (5-p)( 4+3p)= 20 +15p -4p-3p²= 20 +11p -3p²
Szczegółowe wyjaśnienie:
Odpowiedź:
a)
(p + 4)(p - 2) = p² - 2p + 4p - 8 = p² + 2p - 8
b)
(-3 + a)(a - 4) = -3a + 12 + a² - 4a = a² - 7a + 12
c)
(2x + 5)(x + 3) = 2x² + 6x + 5x + 15 = 2x² + 11x + 15
d)
(4m + 1)(2m - 5) = 8m² - 20m + 2m - 5 = 8m² _ 18m - 5
e)
(5 - p)(4 + 3p) = 20 + 15p - 4p - 3p² = -3p² + 11p + 20
Szczegółowe wyjaśnienie: